Centrifuge study on the effect of pile bending stiffness on the slope stabilised by piles. Issue 4 (27th July 2020) - Lei, Guoping; Wu, Wei
Abstract : The stability and failure of a slope stabilised by piles are influenced by the pile bending stiffness. In this paper, the effect of the bending stiffness is studied by centrifuge model tests. Two kinds of piles made of aluminium and acrylic tubes are chosen to represent relatively rigid and flexible piles, respectively. The piles are installed in a row at various pile-spacing ratios in a slope with an inclination of 45°. The model slope consists of a compacted inclined soil layer sliding on a stable wooden structure along a prescribed slip surface. Strain gauges are installed on an aluminium pile to obtain the bending moment. Images taken during the test from the side and the top are used to monitor the soil and pile displacements. The results show that the slope is well stabilised by aluminium piles with small spacing. In the case of relatively flexible piles, the top part of the pile becomes ineffective and the slope stability is reduced.